MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VII SMP NEGERI 1 MERAUKE MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE AUDITORY, INTELLECTUALY, AND REPETITION - Etriana Meirista; Margaretha Roya (Musamus University, 2019)
Abstract: This study aims to improve students' mathematics learning achievement using auditory, intellectualy, and repetition (AIR) type of cooperative models in Class VII material fractions. This research is a research action class is done in 2 cycles. Each cycle is divided into four parts. They are planning, implementation, observations, and reflection. These research subjects are students of class VII SMP Negeri 1 Merauke totaling 32 students. Data collection techniques were used that test, observation and questionnaire responses of students. The research results showed that the average value of students increased at every cycle as well as the classical completeness of the cycle I namely 62,50% and cycle II 90,62% of those results show that an increase in classical from cycle I to cycle II. Student activity increase in cycle I gained 50,00% with a high category and cycle II retrieved 84,38% with category is very high, so it can be concluded that the application of the model of cooperative type auditory, intellectualy, and repetition can improve results of learning mathematics class VII students learn mathematics SMP Negeri 1 Merauke. Keywords: result of learning, cooperatif learning, the type of AIR.